The effectiveness of education or behavioral interventions on adherence to phosphate control in adults receiving hemodialysis: a systematic review protocol. (March 2015) - Milazi, Molly; Bonner, Ann; Douglas, Clint
Abstract : Review question/objective : The objective of this review is to identify the effectiveness of education or behavioral interventions on adherence to phosphate control in adults with end stage kidney disease (ESKD) receiving hemodialysis (HD). Background : Hyperphosphatemia occurs in people with ESKD as a result of the kidneys' reduced ability to excrete an ingested phosphate load.1, 2 Hyperphosphatemia significantly lowers the serum calcium concentration, stimulating the release of parathyroid hormone (PTH), causing secondary hyperparathyroidism.3–6 In ESKD, hyperphosphatemia also slows the activation of vitamin D which leads to impaired absorption of calcium from the gastrointestinal tract, resulting in reduced mobilization of calcium and phosphate from the bones, and causing metabolic bone disease.2, 6, 7 The reduced mobilization of both phosphate and calcium enables these two minerals to bind together creating a calcium‐phosphate product. At a serum concentration of >1.78mmol/L the calcium‐phosphate product crystallizes and is deposited within the soft tissue and vasculature.6, 8, 9 In ESKD the development of vascular calcification of the arterial media (i.e. calciphylaxis) is a major contributing factor of morbidity and mortality.4, 5, 9, 10 Methods of phosphate control Hyperphosphatemia is a wellrecognized risk factor for renal osteodystrophy and cardiovascular mortality in people with ESKD.1, 4, 11 Collectively this is called chronic kidney disease ‐ mineral bone disorder (CKD‐MBD). Treatment of hyperphosphatemia requires a combination of dietary phosphate restrictions, use of oral phosphate binder therapy to reduce intestinal phosphate absorption, vitamin D3 (calcitriol) supplementation and adequate dialysis prescription to promote removal of phosphate.12–15 The treatment goal is to maintain serum phosphate levels at near normal, 0.7 ‐ 1.6mmol/L (3.5 ‐ 5.5 mg/dL)16, and that sustained control of serum phosphate is a strong predictor of improved survival in people receiving HD.11 However approximately 40% of patients receiving HD have a serum phosphate level of >1.6mmol/L.16 Dietary phosphate restriction The implementation of dietary phosphate restrictions is the first step in treating hyperphosphatemia. The average daily adult diet contains approximately 800‐1500mg of phosphate which is absorbed mostly in the duodenum and jejunum.17 However, there is a linear relationship between phosphate and protein intake.1 In general, foods high in phosphate such as milk and meat are rich in protein. For each gram of protein, there is approximately 13‐15mg of phosphate.17 The recommended protein intake for a HD patient is 0.8g per kg of body weight per day.7, 18 However, the dietary restrictions necessary to sustain acceptable serum phosphate in HD patients could lead to protein malnutrition.4, 7, 19 Therefore, dietary phosphate restriction is not sufficient to control serum phosphate levels to current national/international guidelines.19 Phosphate binders The mainstay treatment of hyperphosphatemia is the use of oral phosphate binder medication.1, 20 Phosphate binders lower phosphate absorption in the intestines by binding to and sequestering phosphate in the gastrointestinal tract, forming insoluble products that are not readily absorbed.21 The Dialysis Outcomes and Practice Patterns Study (DOPPS) involving 23, 898 patients on HD at 923 facilities in 12 countries found that 88% of patients were prescribed phosphate binders and 12% were not. This study found a 25% lower mortality rate (HR, 0.75; 95% CI, 0.68‐0.83) in patients who were prescribed phosphate binders versus those not prescribed phosphate binder medication.11 However, most people receiving phosphate binding medication do not achieve target serum phosphate level.3 Hemodialysis The basic conventional four‐hour thrice‐weekly HD removes approximately 700‐1, 000mg of phosphate per session, resulting in a weekly reduction of 2100‐3000mg.8, 21, 22 Effective phosphate removal through HD is complicated by phosphate's biphasic elimination from the body. Kinetic studies have shown that serum phosphate levels drop rapidly in the first one to two hours of HD treatment and then reach a plateau.8, 22 Soon after HD, a rebound of serum phosphate occurs to a rise of about 30‐40%. This is because of the slow influx of elements to the extracellular space after a standard HD session.3, 8, 22 It has been recognized that increasing dialysis frequency or duration leads to reduced serum phosphate.19 Data from the Frequent Haemodialysis Network nocturnal trial showed that daily or extended nocturnal HD led to an average decrease in serum phosphate levels of 0.4mmol/L (95% CI: 0.3‐0.7mmol/L) compared with conventional four‐hour thrice‐weekly HD treatment.23 In spite of the relatively low removal rates of phosphorus achieved by HD it is indicative that HD alone cannot correct the phosphate levels that are associated with the usual dietary content of phosphate.21, 22 Therefore, successful treatment of hyperphosphatemia requires patients adhering to a combination of dietary phosphate restrictions, 8 use of oral phosphate binder therapy to reduce intestinal phosphate absorption21 and adequate HD prescription to promote removal of phosphate.24 Adherence to phosphate control Research on adherence to phosphate control dates back to 1960.14 However, the use of education and behavioral interventions to improve long term adherence to phosphate control has been subjected to less investigation in people with ESKD. Several research studies indicate education and behavioral interventions could help individuals change their behavior and hence increase adherence to phosphate control.5, 13, 20, 25, 26 A number of studies have used different educational interventions, carried out by either nurses or dieticians. The education sessions were one‐on‐one or group, and verbal or video was used to provide the education.13, 14, 27, 28 Also, structured psychological approaches aimed at helping patients to change their beliefs, consequently developing healthy behavior, have been used to produce positive results in improving adherence to diet, medication and HD treatment.28–31 These studies illustrate that theoretical and empirically based behavioral approaches are feasible and can result in a positive reduction of serum phosphate level. However, further developments of clinically useful behavioral and educational strategies are needed to sustain long term adherence with phosphate control. A literature search of the Cochrane central register of controlled trials, JBI, Prospero international prospective register of systematic review and Campbell collaboration systematic reviews was conducted and only one systematic review of relevance to this topic was found. This systematic review was of randomized controlled trials of educational and counselling interventions to improve dietary phosphate adherence in both HD and pre‐dialysis patients.26 However, this systematic review did not include all treatment methods that are used in combination to control phosphate. The control of serum phosphate levels in people receiving HD continues to be a challenge for practitioners and is of clinical significance to patient outcomes. If left untreated hyperphosphatemia significantly increases the risk of morbidity and mortality in people with ESKD.12 It is important to review studies that have been undertaken comparing the outcomes of education and behavioral interventions, regardless of study design, targeting patient adherence to dietary phosphate intake, phosphate binder medication and HD treatment.